INFLUENZA A/H10 VIRUSES OF WILD BIRDS, MAMMALS AND HUMANS - Zhumatov , K.Kh.; Kydyrmanov , A.I. (Eurasian Journal of Applied Biotechnology, 2019)
Emerging infectious diseases pose a serious threat to wildlife, domestic animals, and public health. Of the more than 335 human infectious diseases that have emerged over the past six decades, influenza is one of the most common infection, causing up to 650,000 deaths per year. In addition to the annual seasonal influenza A, the emergence of its new, pandemic, and highly pathogenic variant is even more dangerous. This review describes the classification of influenza pathogens, their structural features, and sources of isolation. The latest published data on the structure, ecology, phylogenesis and pathogenicity of influenza A subtype H10 viruses from various host species are summarized. It is noted that the avifauna is not the only possible reservoir for H10 influenza viruses; avian H10N8 infected dogs in China and mink in Scandinavia, and H10N7 caused widespread mortality of seals in the Baltic Sea in 2014. The first three human cases of avian influenza A H10N8 were reported in 2013-2014 in China, one of which lead to mortality. Information is provided on the genetic variability and evolution of influenza A subtype H10 strains circulating in avifaunal, mammalian, and human populations. Influenza A subtype H10 virus is actively evolving by exchange of genetic information. The potential epidemiological hazard of influenza A virus (H10N8) is as a causative agent of a pandemic, and the need to control its circulation in populations of birds, mammals and among the people is emphasized.